Multistatic Data Matrix Mixed Eigenvector Processing for Time-Reversal Imaging - Zhou, Qiping; Teixeira, Fernando L. (IEEE geoscience and remote sensing letters, 2025)
In this work, a new array imaging algorithm is proposed that combines the relative advantages of two widely used subspace methods for microwave imaging: multiple signal classification (MUSIC) and time-reversal operator decomposition (DORT, under its French acronym). For the examples considered, the proposed algorithm yields a better imaging performance (in terms of resolution and selective focusing ability) than DORT and an imaging performance similar to MUSIC. At the same time, it provides a reduced computational burden of about 20% relative to that of MUSIC and only a slight increase relative to DORT.